Evaluation of the Practice Pattern of Medical Patients' VTE Prophylaxis With a Standard Risk Assessment Model Form: MERAM Study. (July 2015) - Ongen, Gul; Demir, Muzaffer; Molinas, Nil; Ince, Birsen; Ongen, Zeki
Hospitalized acutely ill patients face high risk for venous thromboembolism (VTE) unless appropriate thromboprophylaxis is applied. This study aimed to determine VTE prophylaxis practices for inpatients in Turkey and to evaluate the impact of physicians' training via a modified "Standard Medical Patients' VTE Risk Assessment Model (MERAM)." A total of 607 inpatients included in this national multicenter noninterventional observational registry were evaluated in terms of demographics, VTE risk, and preventive measures at 2 consecutive cross-sectional visits. Physicians were asked to complete a questionnaire on current VTE method risk assessment and other models including MERAM. The VTE prophylaxis rates significantly increased from 49.4% to 62.4% between visits ( P < .05). The lack of risk evaluation decreased from 74.6% to 19.5% ( P < .001). Percentage of physicians using prophylaxis and use of MERAM increased between visits. Physician training proved effective for providing general "awareness" of VTE prophylaxis and led to higher rates of risk assessment model-based appropriate VTE prophylaxis.